Mercado de IPOs: uma comparação entre períodos de crise - Castagno, Pedro Affonso Rachas (Universidade Federal de São Carlos, 2024)
During the most significant global crises of recent times – the Subprime Crisis between 2007-2008 and the COVID-19 Pandemic between 2020-2021 – Brazil observed the highest volumes of IPOs (initial public offerings) in its history. In this context, this paper aims to discuss what motivated this large number of offerings, even in challenging times, and to assess how macroeconomic variables relate to and influence IPO activity. To this end, the study method involved a literature review and descriptive data analysis. The period evaluated was from the fourth quarter of 2004 to the fourth quarter of 2023, covering the two crisis moments in question and also providing a comparison with previous and subsequent periods. As a result, it was found that the Selic rate had a significant and inversely proportional relationship with IPOs. Inflation, although not having an immediate direct relationship with IPOs, influences the Selic rate, indirectly affecting the IPO market. GDP showed a positive correlation with the number of IPOs. The exchange rate, despite significant fluctuations, shows a weak relationship with IPOs, reflecting more the outflow of foreign capital than the issuance of shares.
IPO market: a comparison between crisis periods
Keywords: IPO; Mercado de Capitais; Ações; Capital Markets; Stocks; CIENCIAS SOCIAIS APLICADAS::ECONOMIA